Molecular Absorption Scanning and Assay of Serotonin Reception Inhibitor Antidepressant Drugs - Santana Silva, Amanda; de Paula, Victor Hugo A.; dos Santos Xavier, Lucas Gabriel; da Silva, Ludimila Nascimento; Silva Lucas, Ana Carolyne; Lourenço Alves, Aléxia Mariany; dos Santos, Fernando Machado (Current Pharmaceutical Analysis, 2024)
Background: Spectrophotometric techniques are based on the absorption of electromagnetic energy by the molecules of the substance analyzed and can be applied to drug analysis. Objective: This study has been proposed to carry out molecular absorption scanning and assay in the ultraviolet region of generic antidepressant drugs of the serotonin reuptake inhibitor class produced by three Brazilian laboratories, addressing the importance of good manufacturing practices, drug quality control, and the use of qualitative and quantitative analytical techniques. Methods: The physicochemical analyses were performed in a Marte Científica (580 UVP) UV-Vis spectrophotometer, and the result was evaluated according to the acceptance interval described in the Brazilian Pharmacopoeia. Results: When calculating the dosage of the fluoxetine hydrochloride sample, the value of 90.95% was obtained and, therefore, the drug was approved for the dosage test. The dosage test for the drugs, citalopram hydrobromide and sertraline hydrochloride, was also approved, obtaining values of 102.4% and 98.2%, respectively. Conclusion: The results presented provide future perspectives regarding the rigor of the need for good drug handling practices, maintenance and qualification of quality control laboratory equipment, and the guarantee of validation of analytical methodologies used in the pharmaceutical industries, contributing to the improvement of the quality of production and pharmaceutical products analysis.
Keywords: neurotransmitters